2018
DOI: 10.1093/geront/gny049
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety Among Partner and Offspring Carers of People With Dementia: A Systematic Review

Abstract: Several important risk factors for carer depression were highlighted in this review. However, a lack of measurement precision and a reliance on cross-sectional studies limits our understanding of exactly how depression and anxiety progress during the caregiving experience. The implications for prevention and intervention programs for depression and anxiety are discussed, as well as suggestions for future research to improve the quality of research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 42 publications
4
65
1
1
Order By: Relevance
“…There are many stages to caring and indeed the nature and type of care varies depending on the needs of the person receiving the care (São José, 2018). Many studies have reported the negative impact of care-giving, particularly on those who care for people living with dementia who may experience clinical depression or anxiety or other less-severe psychological impacts (Cross et al, 2018; Ryan et al, 2018; Wang et al, 2018; Watson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are many stages to caring and indeed the nature and type of care varies depending on the needs of the person receiving the care (São José, 2018). Many studies have reported the negative impact of care-giving, particularly on those who care for people living with dementia who may experience clinical depression or anxiety or other less-severe psychological impacts (Cross et al, 2018; Ryan et al, 2018; Wang et al, 2018; Watson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence shows conflicting results on whether caring for a dependent older person impacts negatively on the physical and emotional health of the caregiver [7,8]. The negative emotional consequences are the most important, with anxiety being one of those with the greatest impact and transcendence [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although many family carers nd their role rewarding, caring responsibilities can incur a signi cant psychological and physical burden. Unless they are well resourced and supported, carers may nd themselves at heightened risk of depression and anxiety, and consequently with poor quality of life [2]. A consequence of unalleviated caregiver burden may be earlier admission to residential care for the person with dementia, leading to a lower quality of life for them and increased pressure on social care services.…”
Section: Background and Rationalementioning
confidence: 99%